(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
The article aims to introduce a theoretical debate about the ideas that dialogue with the decolonial perspective applied to fashion, as well as to bring the theoretical developments listed in the context of the global South. For this purpose, it employs a group of fashion scholars who have, since the mid-1990s, been examining fashion key concepts, specifically the Fashion concept itself. Thus, the article inquiries the fashion authorization system and the belief of Fashion is a exclusively Western manifestation. The review is directed to the colonial matrix of thought that produces and reproduces a binary division between societies, which are subjected to the classification that opposes them between “with fashion” or “non fashion”.